1987
DOI: 10.1042/bj2450609
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of serine metabolism in hepatoma 3924A during different phases of cellular proliferation in culture

Abstract: The activities of 3-phosphoglycerate dehydrogenase and serine hydroxymethyltransferase increased markedly during the transition of hepatoma cells from a resting non-proliferating culture into the proliferating growth phase. Activities declined as cells reached confluency and entered the plateau growth phase. This pattern was paralleled by changes in [14C]serine incorporation into nucleic acids. The experiments support the hypothesis that the biosynthesis of serine is metabolically coupled to its utilization fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 17 publications
2
60
0
2
Order By: Relevance
“…Both the incorporation of the h-carbon of serine into DNA and SHMT1 activity are increased when cells are stimulated to proliferate (44). SHMT1 activity is also elevated in tumor tissues (45).…”
Section: Discussionmentioning
confidence: 99%
“…Both the incorporation of the h-carbon of serine into DNA and SHMT1 activity are increased when cells are stimulated to proliferate (44). SHMT1 activity is also elevated in tumor tissues (45).…”
Section: Discussionmentioning
confidence: 99%
“…These lipids are essential for cellular proliferation (24). The metabolic role of L-serine as a major source of one-carbon units for de novo synthesis of purine nucleotides and the pyrimidine nucleotide deoxythymidine monophosphate also supports this possibility (25). Finally, the microcephaly evident in the Phgdh null embryos (Figs.…”
Section: Phgdh Expression In Mutant Embryosmentioning
confidence: 94%
“…This considerably reinforces the generality of the hypothesis (Snell, 1984) that the increased capacity for serine synthesis in cancer cells is coupled to its preferential utilization for the provision of nucleotide precursors. In hepatoma cells in different phases of growth in culture it has been established that the changing activity of serine hydroxymethyltransferase correlates with the flux of 14C-serine into purine and pyrimidine bases of cellular nucleic acids (Snell et al, 1987). The importance of serine metabolism for the replication of cancer cells is emphasised by their increased capacity to synthesize serine de novo rather than simply relying on the uptake of this amino acid from the extracellular fluid.…”
Section: General Conclusion and Implications For Anti-cancer Therapymentioning
confidence: 99%
“…During cellular proliferation the demands for increased nucleotide biosynthesis for DNA replication will have to be matched by a corresponding increase in serine utilisation for nucleotide precursor formation. Indeed, recent studies have shown enhanced 14C-serine incorporation into nucleotides during the transition of cells from the quiescent to proliferative growth phases in mitogenically-stimulated lymphocytes (Eichler et al, 1981;Rowe et al, 1985) and in hepatoma cells (Snell et al, 1987) in culture. Serine hydroxymethyltransferase promotes serine utilization for this purpose, and its activity increases in parallel with serine incorporation into nucleotides in the above situations (Eichler et al, 1981;Thorndike et al, 1979;Snell et al, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation